Food safety knowledge, attitude, and practice of consumers in Malaysia: a review - Aspian, N.A.; R., Tunung; Jamaluddin, F.; Ismail, Z.; Sharkawi, I.; Alan, R.; Lepun, P.; Rosli, A.; Nillian, E.; Anyi, U. (Rynnye Lyan Resources, 2024)
Food safety is a crucial issue in every country. Without a good food safety system, a country will suffer economically and socially. This paper aims to revisit the literature on food safety knowledge, attitude, and practice in Malaysia and globally. Foodborne illnesses are caused by food that has been contaminated at any stage of the food production, delivery, and consumption chain. Non-compliance with food handling guidelines linked to a lack of food safety awareness was the leading cause of foodborne illnesses. This paper highlighted consumers’ role in preventing foodborne diseases by following food safety recommendations when preparing food at home. Hence, studies on consumers' food safety knowledge, attitude, and practice are very important for future development programs on food safety guidelines, and to ensure successful implementations.